Educational Themes and Teacher Roles in How Teachers Can Help Kids Find Their Political Voices by Sydney Chaffee - Nawawi, Muhammad; Suryawati, Sri Suci (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This study examines the educational themes and teacher roles presented in Sydney Chaffee’s speech, How Teachers Can Help Kids Find Their Political Voices. The research identifies two major categories—educational themes and teacher roles—each encompassing several sub-themes that reflect Chaffee’s philosophy of civic education. Key educational themes include education as a tool for social justice, relevance to real-world issues, development of civic engagement skills, critical historical awareness, and promotion of student voice and activism. Teacher roles highlighted in the speech include facilitating difficult conversations, supporting student activism, acting as risk-takers and change agents, encouraging critical thinking, and building trust-based learning environments. Findings suggest that Chaffee views teaching as inherently political and transformative, positioning the classroom as a space for fostering democratic values, critical awareness, and active citizenship. This perspective challenges traditional content-focused instruction by integrating social justice and civic empowerment into daily teaching practice. The study concludes that such an approach can strengthen students’ political agency, provided teachers receive adequate support, training, and autonomy to address sensitive civic topics.